EFFECT OF ESSENTIAL OILS ON THE “in vitro” MICELIAL GROWTH OF THE FUNGUS Lasiodiplodia theobromae - Lopes Viana, Talita; Moya Peres, Walmor; Queiroz David, Grace; Lopes de Matos, Dilânia; Ribeiro Campos, Ostenildo; Oscar Mitsuo Yamashita, Prof; Antonio Camillo de Carvalho, Marco; Cezar Ceresini, Paulo (South American Journal of Basic Education, Technical and Technological, 2020)
Studies have shown that plant essential oils have the potential for alternative control of several economically important crop diseases. The objective of this work was to evaluate the effect of garlic (Allium sativum L.), coconut (Cocos nucifera L.), copaiba (Copaifera landesdorff), castor bean (Ricinus communis L.) and melaleuca (Melaleuca alternifolia) essential oils on mycelial growth. fungus Lasiodiplodia theobromae at non-toxic concentrations to plants. The experiment was carried out at the UNEMAT Microbiology and Phytopathology Laboratory. The experimental design was completely randomized with five treatments and one control, using five replications. From the growth averages, the Mycelial Growth Speed ​​Index (IVCM) and the Growth Inhibition Percentage (GIP) were obtained. Data were subjected to analysis of variance, followed by Tukey test at 5% significance level. All treatments had good results in controlling the mycelial growth of the fungus L. theobromae, and the treatments with melaleuca and coconut essential oil showed the best results and did not differ statistically.